A new species of Minagrion Santos, 1965 (Odonata: Coenagrionidae) from the Cerrado of Northern Minas Gerais state, Brazil - Vilela, Diogo Silva; Jacques, Gabriel De Castro; Souza, Marcos Magalhães De (Zootaxa, 2023)
Minagrion veredae sp. nov. (Holotype ♂, BRAZIL (Z329), Minas Gerais state, Grande Sertão Veredas National Park, 15.iv.2023, (15°6’ S, 45°48’ W, 660 to 900m asl), P.S. Vital leg.) is described, illustrated and diagnosed based on specimens collected at the Grande Sertão Veredas National Park. The new species inhabits palm swamp environments, Cerrado domain phytophysiognomy, as it is typical of other species of the genus. It can be diagnosed from its congeners mainly by the forcipate shape and large teeth of the cercus and the lanceolate shape of segment two of the genital ligula.